Design and simulation studies of low power tuneable gyrotrons for DNP/NMR spectroscopy Applications - Singh, Rajanish Kumar (IIT(BHU) Varanasi, 2020)
Abstract available in content.
Keywords: Design and simulation; studies of low power tuneable gyrotrons for; DNP/NMR spectroscopy Applications